2010
DOI: 10.1182/blood-2009-11-253062
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and selective detection of free FXIII activation peptide: a potential marker of acute thrombotic events

Abstract: Coagulation factor XIII (FXIII) stabilizes fibrin fibers and is therefore a major player in the maintenance of hemostasis. FXIII is activated by thrombin resulting in cleavage and release of the FXIII activation peptide (AP-FXIII). The objective of this study was to characterize the released AP-FXIII and determine specific features that may be used for its specific detection. We analyzed the structure of bound AP-FXIII within the FXIII A-subunit and interactions of AP-FXIII by hydrogen bonds with both FXIII A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
(26 reference statements)
1
18
1
Order By: Relevance
“…It was reported recently that the FXIII AP is free in solution after IIa cleavage and available for binding to monoclonal antibodies specific to FXIII-AP [48]. Our HDX results suggest that in the presence of Ca 2+ the unhydrolyzed AP remains tightly associated with FXIII A 2 .…”
Section: Discussionsupporting
confidence: 54%
“…It was reported recently that the FXIII AP is free in solution after IIa cleavage and available for binding to monoclonal antibodies specific to FXIII-AP [48]. Our HDX results suggest that in the presence of Ca 2+ the unhydrolyzed AP remains tightly associated with FXIII A 2 .…”
Section: Discussionsupporting
confidence: 54%
“…Activation peptides of zymogens are mostly viewed merely as structures occluding the catalytic center or stabilizing the inactive conformation. Recombinant FXIII lacking AP‐FXIII has not been expressed to date, although we have previously demonstrated that AP‐FXIII dissociates from the dimer upon thrombin cleavage . In this study, we present evidence that AP‐FXIII is vital for the stability of FXIII.…”
Section: Discussionmentioning
confidence: 60%
“…However, it is challenging to unravel what is due to a general reduction of HDAC activity vs specific effects via HDAC1 and/or HDAC2. These observations are in some contrast to the general concept of HDAC function, which posits that cancer cells (often) have elevated HDAC activity that helps them to proliferate (eg, by directly repressing some of the small cyclin-dependent kinase inhibitor genes, such as p21 or p57 6,7 ). In this classical scenario, HDAC inhibition counteracts uncontrolled cellular proliferation and is therefore beneficial.…”
contrasting
confidence: 46%
“…4 Then, my group developed the first enzymelinked immunosorbent assay method using antibodies directed specifically toward free AP-FXIII and showed that AP-FXIII is indeed released into plasma following FXIII activation by thrombin. 5,6 We were also able to present first measurements of in vivo-generated free AP-FXIII circulating in plasma of patients with an acute thrombotic event. The characterization of the processes on the molecular level has implications for the better understanding of these processes and also for development of new therapeutic strategies.…”
mentioning
confidence: 97%